2000
DOI: 10.1046/j.1365-2036.2000.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nabumetone in osteoarthritis: emphasis on gastrointestinal safety

Abstract: The results suggest that nabumetone was similar in efficacy by most criteria to diclofenac SR and piroxicam in relieving the symptoms of osteoarthritis; however, nabumetone's GI safety profile was generally superior to that of both comparator NSAIDs. In the pooled analysis, nabumetone was associated with a significantly lower total incidence of ulcers and bleeding events, and a significantly lower incidence of complications associated with these events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In patients with rheumatoid arthritis or osteoarthritis, the efficacy of diclofenac sodium sustained-release formulation was comparable to that of nabumetone [ 118 ] and meloxicam [ 119 ]. Furthermore, in patients with chronic pain due to osteoarthritis of the hips and/or knees, diclofenac sodium extended-release tablets were shown to be as effective as controlled-release tramadol, an opioid analgesic [ 120 ].…”
Section: Oral Preparations Of Diclofenac Sodiummentioning
confidence: 99%
“…In patients with rheumatoid arthritis or osteoarthritis, the efficacy of diclofenac sodium sustained-release formulation was comparable to that of nabumetone [ 118 ] and meloxicam [ 119 ]. Furthermore, in patients with chronic pain due to osteoarthritis of the hips and/or knees, diclofenac sodium extended-release tablets were shown to be as effective as controlled-release tramadol, an opioid analgesic [ 120 ].…”
Section: Oral Preparations Of Diclofenac Sodiummentioning
confidence: 99%
“…We excluded 497 citations after excluding duplicates and screening titles/abstracts. The full texts of the remaining 68 records were screened and 36 trials including 112,351 participants from 35 publications were finally included 3 , 25 – 58 (there are 2 trials reported in a same paper, 28 see the flowchart of study selection in Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disease-modifying drugs such as methotrexate, sulfasalazine, gold compounds, penicillamine, and chloroquine improve symptoms and can reduce disease activity in RA, such as reduction in number of swollen and tender joints, pain score, disability score, and rheumatoid factor. DMARDs are often referred to as secondline drugs, and some have a place in the treatment of other chronic inflammatory diseases [79][80][81].…”
Section: Adverse Effects Of Currently Used Nsaid Therapiesmentioning
confidence: 99%